2002
DOI: 10.1207/153744202753604449
|View full text |Cite
|
Sign up to set email alerts
|

Transporting Efficacious Treatments to Field Settings: The Link Between Supervisory Practices and Therapist Fidelity in MST Programs

Abstract: Validated a measure of clinical supervision practices, further validated a measure of therapist adherence, and examined the association between supervisory practices and therapist adherence to an evidence-based treatment model (i.e., multisystemic therapy [MST]) in real-world clinical settings. Evidence of linkages between supervisor adherence to the MST supervisory protocol, as assessed through therapist reports, and therapist adherence to MST principles, as assessed through caregiver reports, was obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 0 publications
2
111
0
Order By: Relevance
“…However, we also note that future research needs to explore the mechanisms that underlie successful large-scale program implementation and contribute to program effectiveness. Although we were not able to examine the mechanisms that may contribute to effectiveness of statewide implementation of MST, research suggests that fidelity to treatment is a critical factor in fostering successful program implementation and positive program effects (Brunk et al 2014; Lofholm et al 2014; Schoenwald et al 2008; Henggeler et al 2002). In Rhode Island, preliminary caregiver reports of clinicians’ treatment fidelity suggest high (above the national MST target) adherence to treatment for the five Rhode Island MST providers (Rhode Island 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also note that future research needs to explore the mechanisms that underlie successful large-scale program implementation and contribute to program effectiveness. Although we were not able to examine the mechanisms that may contribute to effectiveness of statewide implementation of MST, research suggests that fidelity to treatment is a critical factor in fostering successful program implementation and positive program effects (Brunk et al 2014; Lofholm et al 2014; Schoenwald et al 2008; Henggeler et al 2002). In Rhode Island, preliminary caregiver reports of clinicians’ treatment fidelity suggest high (above the national MST target) adherence to treatment for the five Rhode Island MST providers (Rhode Island 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics include specific reasons for MST referral, parent-related data (e.g., parenting practices and skills), dosage or intensity of treatment, and fidelity to treatment measures. For example, studies have shown that factors such as parenting practices (Asscher et al 2013; Tighe et al 2012) and fidelity to treatment (Brunk et al 2014; Henggeler et al 2002) are important mechanisms of change in MST. In addition, we did not have information on whether supplementary or other types of treatment were received by our treatment group and whether our comparison group received some type of treatment (e.g., usual services) during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…methods of environmental control, differences between use of rescue and controller medications, using asthma action plans for symptom management, etc). Quality assurance protocols also included use of a manual on use of MST with youth with high-risk asthma developed during a feasibility trial 27 feedback on therapist and supervisor fidelity to MST procedures 28,29 and audiotaping of all treatment sessions for supervisory review and fidelity coding.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations from parents and children did not reveal any occurrences of negative drift, but could have done so if asking specifically about intervention components and conduct, such as in the evaluation routines of MST (Henggeler, Schoenwald, Liao, Letourneau, & Edwards, 2002). …”
Section: Case Narrativementioning
confidence: 99%